Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.3329/bjpbg.v24i1.16999
|View full text |Cite
|
Sign up to set email alerts
|

GENETIC VARIABILITY AND CHARACTER ASSOCIATION FOR AGRONOMIC TRAITS IN HYBRID RICE (Oryza Sativa L.)

Abstract: Twenty four hybrid rice varieties of diverse origin were studied for genetic variability, correlation and path analysis under medium high land of Gazipur. The PCV values were greater than GCV, revealing little influence of environment in character expression. High values of heritability along with moderate genetic advance were observed for panicle/m 2 , days to 50% flowering and plant height. Grain yield showed positive significant association with number of effective tillers/hill, panicle/m 2 , spikelet ferti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 7 publications
(6 reference statements)
9
18
0
Order By: Relevance
“…The results suggest that negative correlations with filled grains leads to lower yield which means early maturing varieties produced lower yields. These results are in accordance with the results of Hasan et al, (2013), who found days to 50% flowering was negatively correlated with yield.…”
Section: Resultssupporting
confidence: 83%
“…The results suggest that negative correlations with filled grains leads to lower yield which means early maturing varieties produced lower yields. These results are in accordance with the results of Hasan et al, (2013), who found days to 50% flowering was negatively correlated with yield.…”
Section: Resultssupporting
confidence: 83%
“…Table 3 Chakravorty and Ghosh (2014) recently found the direct positive effect of grain length on panicle yield. Hasan et al,(2013) found the direct positive effect of fertility % of spikelets on primary branches panicle -1 on grain yield. Negative direct effects on panicle yield were exhibited by grain breadth (-0.924) and grain length/breadth ratio (-0.753).…”
Section: Resultsmentioning
confidence: 99%
“…Whereas the control had a mean grain weight of 2.89 g, superior mutant families presented a mean value of 4.40 g. This result observed in these mutants can be related to a greater yield, since the grain mass is a major component of yield (Jeng et al 2006;Song et al 2007;Hasan et al 2013;Karim et al 2014). It is worth emphasizing that this increase in the main panicle grain weight will be relevant provided that there is no reduction in other components of grain yield.…”
Section: Vk Luz Et Almentioning
confidence: 92%